Preposition Repetition in Phrases with Homogeneous Parts of a Sentence in Business Texts of the 18th Century - A. S. Ulitova (Научный диалог)
The question of dialect differences in the use of homogeneous parts of a sentence and prepositions in business texts of the 18th century is considered. Attention is paid to the factors that influenced the preposition repetition in such groups. The results of comparative analysis of peripheral (in particular, Chelyabinsk) and Moscow business texts of the 18th century are presented. The question is raised whether the syntactic role of words in the group under study affected the preposition repetition. Special attention is paid to the duplication of the preposition in a number of stable expressions typical for the business usage of the 18th century. For the first time, the task is to identify differences in the use of repeated prepositions in business texts that relate to different territories. The relevance of the research is due to the fact that it draws readers’ attention to a new aspect in the history of the formation of Russian language norms. It is proved that in the business texts of the 18th century, which have different origins, territorial affiliation was not a decisive factor. The author points out that along with the place where the document was written, the author’s preferences, the functioning of prepositions in formula expressions, the syntactic role of homogeneous members, and the genre of the document may have influenced the duplication of the preposition.